Mismatch Repair Deficiency in Gliomas: A Rare Insight into Microsatellite Instability and Its Diagnostic Implications - Rajendiran, Indhumathi; Ahluwalia, Charanjeet; Shankar, Kepeemadam Balasubramanyam; Arora, Sheetal; Ahuja, Sana (Asian Journal of Neurosurgery, 2025)
Mismatch repair deficiency (MMRD), a hallmark of microsatellite instability (MSI), has been extensively studied in gastrointestinal and endometrial cancers but remains underexplored in gliomas. Deficiencies in mismatch repair (MMR) proteins, such as MLH1, MSH2, MSH6, and PMS2, may contribute to tumor progression, treatment resistance, and responsiveness to immune checkpoint inhibitors. This study aimed to evaluate the expression of MMR proteins in gliomas using immunohistochemistry (IHC) and analyze their association with patient age, histological subtype, and central nervous system (CNS) World Health Organization (WHO) (2021) tumor grade.A total of 64 glioma cases were retrospectively analyzed, including a range of histologic subtypes and grades. IHC for MLH1, MSH2, MSH6, and PMS2 was performed to detect MMR protein expression. Cases showing MMR deficiency by IHC were further evaluated using next-generation sequencing (NGS) for MSI and frameshift mutations in MMR genes. Statistical analyses were conducted to assess associations with clinicopathological parameters.Quantitative variables were expressed as mean and standard deviation. Quantitative variables were expressed as percentage or proportion. Chi-square test and Fisher's exact test were done to associate MMR protein deficiency with age, histopathological type, and CNS WHO grade of glioma. p-Value of <0.05 was considered significant.MMR deficiency was observed in 3 of 64 cases (4.69%), all showing isolated loss of MSH6 expression. These included two IDH-mutant astrocytomas and one pilocytic astrocytoma. No significant associations were found between MMRD and age (p = 1.000), histological subtype (p = 0.448), or WHO grade (p = 0.448). NGS revealed one MSI-high and one MSI-low tumor, both harboring frameshift mutations in multiple MMR genes.MMR deficiency is rare in gliomas, with isolated MSH6 loss being the most common finding. While not significantly associated with tumor grade or patient demographics, MMRD may have clinical relevance in specific subgroups. NGS findings highlight the potential utility of integrating molecular diagnostics for identifying MSI and guiding immunotherapy decisions.
Keywords: mismatch repair protein; microsatellite instability; glioma; immunohistochemistry; astrocytoma